Organic matter source and thermal maturity within the Late Cretaceous Niobrara Formation, U.S. Western Interior. (September 2017) - Tessin, Allyson; Bianchi, Thomas S.; Sheldon, Nathan D.; Hendy, Ingrid; Hutchings, Jack A.; Arnold, T. Elliott
Abstract: The Late Cretaceous sedimentary record of the North American Western Interior Seaway is characterized by cyclic deposition of organic carbon-rich sediments. One notable interval during the late Coniacian-Santonian is recorded by the Niobrara Formation. The organic carbon-rich interval within the Niobrara Formation has been identified as Oceanic Anoxic Event (OAE) 3. Understanding the reason for this distribution of organic carbon within the Niobrara Formation requires a refined understanding of the source and maturity of the organic matter. In this study, we present lipid biomarker records from the USGS Portland #1 core (Cañon City, CO) to constrain the thermal maturity of the organic matter and the differing contributions of organic matter sources. Sterane and hopane thermal maturity indices indicate that the samples are somewhat immature with respect to oil formation and that there is strong agreement between different proxies for thermal maturity. Based on the distribution of n- alkanes, steranes, and hopanes, there is a significant increase in the contribution of algal organic matter during and after OAE 3, coeval with increased organic carbon accumulation. Although a consistent terrestrial contribution is observed, it is only a minor source of organic matter at the Portland core location and does not drive increased organic matter accumulation during OAE 3. Of particular note is the consistent influence of even-over-odd predominantly mid-chain length (C21 to C25 ) organic matter. This observation within the brackish to marine, not methanogenic WIS represents an expansion of the depositional settings in which even-over-odd predominance has been observed in mid-chain length n-alkanes. Pristane (Pr) and phytane (Ph) abundances are inconsistent with a redox control on Pr/Ph ratios and suggest an increase in the delivery and/or preservation of phototrophic organic matter as the source for pristane and phytane in the Portland core.